Inside Back Cover: Microfluidic systems toward blood hemostasis monitoring and thrombosis diagnosis: From design principles to micro/nano fabrication technologies (View 1/2022). Issue 1 (31st January 2022) - Xu, Yi; Yu, Guang; Nie, Ruqiong; Wu, Zhigang
Abstract : Perioperative monitoring of blood coagulation is critical to guide hemostatic therapies and predict the risk of bleeding during surgical procedures. Up to now, point‐of‐care coagulation monitoring devices still do not fully meet the clinical practice. In article number 20200183, Yi Xu, Zhigang Wu and their co‐workers provide an overview of design principles of microfluidic systems and their micro/nano fabrication strategies in studying the platelet adhesion and aggregation. The importance, benefits and challenges of introduced principles and methods are critically discussed to guide designing more versatile point‐of‐care (POC) devices for hemostasis monitoring and thrombosis diagnosis.